Programmable dual-band acoustic topological insulator with dynamically movable interface states - Ge, Yong (2023)
Topological acoustic interface states in one-dimensional (1D) acoustic topological insulators (ATIs) are zero-dimensional (0D) topological states localized at an interface. Unlike topological edge states that can propagate to deliver information in acoustic waveguides, the 0D topological interface states generally cannot serve as information carriers to deliver information from one location to another due to their intrinsic localization. Here, we design and demonstrate a 1D ATI with a movable interface, enabling the 0D topological acoustic interface states to deliver information from one location to another. The ATI design is based on two types of elemental building blocks—denoted as “1” and “0”—which are programmable. These elements of 1 and 0, when periodically arranged, can form topologically distinct crystals, whose interface hosts acoustic topological interface states in two bandgaps simultaneously. Since these two types of elements can switch from each other with external control, a programmable 1D dual-band ATI can be constructed. By programming coding sequences of 1 and 0 elements, we can observe dynamically movable 0D topological interface states riding on a moving interface along the 1D ATI in both bandgaps. Our work opens an avenue to develop topological acoustic devices with programmable and dynamic functions, which may have a variety of potential applications in the fields of energy trapping, topological pumping, information processing, and sound communication.